Streptococcus, the Predominant Bacterium to Predict the Severity of Liver Injury in Alcoholic Liver Disease - Zhong, Xiaodan; Cui, Ping; Jiang, Junjun; Ning, Chuanyi; Liang, Bingyu; Zhou, Jie; Tian, Li; Zhang, Yu; Lei, Ting; Zuo, Taiping; Ye, Li; Huang, Jiegang; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background New evidence implies that the imbalance of gut microbiota is associated with the progression of alcoholic liver disease (ALD) and that the composition of gut microbiota is altered in ALD patients. However, the predominant bacterium in patients involved in the progress of ALD has not been identified. The purpose of this study is to investigate the predominant bacterium in the early and end-stages of ALD as well as the relationship between the bacterium and the degree of liver injury. Methods We enrolled 21 alcoholic fatty liver (AFL) patients, 17 alcoholic liver cirrhosis (ALC) patients and 27 healthy controls, and sequenced the 16S rRNA gene of their fecal microbiota. The gut microbiota composition and its relationship with the indicators of clinical hepatic function were assessed using canonical correspondence analysis (CCA), spearman correlation heatmap and multivariate association with linear (MaAsLin) Models. Results The composition and structure of gut microbiota changed greatly in different stages of ALD, and the degree of disorder was aggravated with the progression of ALD, even in the early stage. Moreover, the relative abundance of Streptococcus was highly enriched only in patients with ALC (P <0.001), and positively correlated with AST level (P = 0.029). The abundance of Streptococcus distinguished the liver injury of ALC patients from the controls with an area under the receiver-operating characteristic curve (AUC) of 0.877 (P < 0.001). Conclusions These findings indicate that the imbalance of gut microbiota exists at the early and end-stages of ALD, and the degree of disorder is aggravated with the progression of ALD. Streptococcus, as the predominant bacterium, may be a microbiological marker to evaluate the severity of liver injury in ALD patients.